Fixed points of a new type of contractive mappings in complete metric spaces - Wardowski, Dariusz (Fixed point theory and algorithms for sciences and engineering, 2012)
In the article, we introduce a new concept of contraction and prove a fixed point theorem which generalizes Banach contraction principle in a different way than in the known results from the literature. The article includes an example which shows the validity of our results, additionally there is delivered numerical data which illustrates the provided example. MSC: 47H10; 54E50